Identification of a Novel Mutation in SASH1 Gene in a Chinese Family With Dyschromatosis Universalis Hereditaria and Genotype-Phenotype Correlation Analysis - Wu, Nan; Tang, Lili; Li, Xiuxiu; Dai, Yuwei; Zheng, Xiaodong; Gao, Min; Wang, Peiguang (Frontiers in Genetics, 2020)
Dyschromatosis universalis hereditaria (DUH) is a rare genodermatosis characterized by mottled hyperpigmented and hypopigmented macules. SASH1 and ABCB6 have been identified as the causative genes for this disorder. We performed whole exome sequencing on a Chinese family with DUH and genotype-phenotype correlation analysis in DUH and lentiginous phenotype patients. A novel heterozygous missense mutation p.Q518P in SASH1 gene was detected in this family. A majority of patients with SASH1 mutations presented as a distinct clinical phenotype clearly different from that in patients with ABCB6 mutations. Our findings further enrich the reservoir of SASH1 mutations in DUH. The clinical phenotypic difference between SASH1 and ABCB6 variants is suggestive of a close phenotype-genotype link in DUH.